2017
DOI: 10.1530/joe-17-0151
|View full text |Cite
|
Sign up to set email alerts
|

The thermogenic effect of nesfatin-1 requires recruitment of the melanocortin system

Abstract: Nesfatin-1 is a bioactive polypeptide expressed both in the brain and peripheral tissues and involved in the control of energy balance by reducing food intake. Central administration of nesfatin-1 significantly increases energy expenditure, as demonstrated by a higher dry heat loss; yet, the mechanisms underlying the thermogenic effect of central nesfatin-1 remain unknown. Therefore, in this study, we sought to investigate whether the increase in energy expenditure induced by nesfatin-1 is mediated by the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…We have recently reported a non-significant increase in UCP1 mRNA expression in the iBAT of rats 4 h following i.c.v. administration of nesfatin-1, without changes in protein levels despite a significant increase in iBAT temperature [9]. These observations, together with the present data, suggest that nesfatin-1, when given acutely, may affect responsiveness to UCP1 rather than its production.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…We have recently reported a non-significant increase in UCP1 mRNA expression in the iBAT of rats 4 h following i.c.v. administration of nesfatin-1, without changes in protein levels despite a significant increase in iBAT temperature [9]. These observations, together with the present data, suggest that nesfatin-1, when given acutely, may affect responsiveness to UCP1 rather than its production.…”
Section: Discussionsupporting
confidence: 62%
“…Recently, nesfatin-1 has been reported to increase energy expenditure via CNS pathways. By means of direct calorimetry, we could previously show that the central injection of nesfatin-1 increases energy expenditure to the same extent as leptin [6], and that this effect employs the melanocortin system [9].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…To date, information on downstream effector systems of NUCB2/ nesfatin-1 with regard to energy homeostasis has only been collected in experiments employing either central nervous or peripheral administration of nesfatin-1 [2,8]. In these experiments, the melanocortin system has been identified as a crucial mediator of nesfatin-1 action [2,11,33]. Furthermore, we have previously observed that NPY mRNA expression in both hypothalamus and NTS is significantly affected by nesfatin-1 administration [8].…”
Section: Discussionmentioning
confidence: 99%
“…reward-related feeding [7], but also increases energy expenditure and core body temperature [8][9][10] by recruiting the melanocortin system [11]. In particular, we identified the interscapular brown adipose tissue (iBAT) as major source of heat production [10,11].…”
Section: Introductionmentioning
confidence: 97%